Perception of Nigerian Films by Christian Youths in Mowe Community - Deborah Oluwadamilola Oyinloye; Perpetua Ogechi Aondover; Omotola Ogunbola; Timothy Ekeledirichukwu Onyejelem (Budapest International Research and Critics University, 2026)
The research work examined, â€œPerception of Nigerian films by Christian youths in Mowe community.â€ The study examined the perception of Christian films by youths of Mowe community with issues such as poor performance and production, which impacts the perception of Christian films negatively. The objectives of this study were to determine the extent of exposure of Christian youths in Mowe community to Nigerian Christian films, examine the perception of Nigerian Christian films among Christian youths in Mowe community, and also explore the influence of Christian films on the religious beliefs and practices of these Christian youths in Mowe community. The research questions were; what is the extent of exposure of Christian youths in Mowe community to Nigerian Christian films, how do Christian youths in Mowe community perceive Nigerian Christian films, and in what ways do these perceptions influence their religious beliefs and practices. Perception theory and cultivation theory were the theories used in this study. The research method used was survey method. This enabled the researcher to objectively collect, evaluate, verify information gathered through the use of questionnaires and synthesize evidence by establishing facts and reaching defensible conclusions. The findings of the study was that a large number of Mowe youths are exposed to Nigerian Christian films, as they frequently watch these films. According to these youths, Christian films do have some improvement to do, even though their movies have a positive impact on their faith. The recommendations were that efforts should be made by Nigerian Christian filmmakers to improve the quality of their films, as they continue to produce films that promotes Christian messages and values.